Alliances as dynamic capability to support organizational transformation: empirical findings from a state-owned enterprise - Priyono, Anjar; Dewi, Elisabeth Ingga; Abdul Halim Lim, Sarina (de Gruyter, 2019)
State-owned companies are typically trapped in a bureaucratic system that means they experience difficulties undertaking changes and adapting to environmental changes. Whenever these companies attempt a strategic maneuver, a series of complex bureaucratic procedures must be followed. As a result, the companies are late in responding to environmental changes. This study discusses how the state-owned companies transform their organization with the support of dynamic capabilities. XT Square, a company owned by the local government in Indonesia, is used as the subject of analysis. XT Square is engaged in property. During the course of its organizational transformation, the company found it difficult to fit with customers’ needs because of the difficulties in understanding market conditions. The company then established alliances with other firms to overcome resource shortages. The results of the analysis demonstrate that the process of building these alliances was not linear; rather, it was iterative in nature. At a certain level, XT Square is required to undertake trial and error. At the end of the paper, a suggestion for further research is provided.